Implementasi Google Clasroom Pada Mata Pelajaran Fikih Kelas VII 2 di MTs. Ma'arif Sidomukti - Ashfarina, Indah Noer; Muyassaroh; Amirudin, noor (STIT Muhammadiyah Paciran, 2021)
There are two impacts for the continuity of education caused by the covid- 19 pandemic. The learning process in schools is the best public policy tool as an effort to increase knowledge. But now the activities taking place at the school have stopped suddenly due to the Covid-19 disruption, therefore the school has shifted the function of the online learning process so that there is no direct interaction between each other. Then the school decided to use the google classroom application which was used as a forum for the process of teaching and learning activities. The purpose of this research is expected. The goal is that this research can be used as a reference for further research on the implementation of learning using e-Learning, besides that for prospective teachers, they can find out how fiqh teachers innovate in implementing google classroom-based learning in MTs. Ma'arif Sidomukti. The research method using interviews and observation. The results of the study concluded that, google classroom is a useful application for online learning and can be followed by many people and can be used for free. The advantage of using the Google Classroom application is that it can add insight and knowledge in Information and Technology (IT) and students can adapt to the virtual world and the problems it faces. The obstacles include internet interference material, there are also students who do not have data, and teachers cannot be optimal in controlling assignments.